2021
DOI: 10.1001/jamanetworkopen.2020.37388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Prenatal Opioid Exposure in Ontario, Canada, 2014-2019

Abstract: This population-based cohort study assesses the prevalence of opioid use in pregnant women in Ontario, Canada, from 2014 through 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…pioid use in pregnancy is a public health concern, [1][2][3][4][5] with 2%-4% of pregnancies exposed to prescribed opi oid analgesics. [6][7][8] Opioid analgesics cross the placenta and have potential to cause fetal harm.…”
mentioning
confidence: 99%
“…pioid use in pregnancy is a public health concern, [1][2][3][4][5] with 2%-4% of pregnancies exposed to prescribed opi oid analgesics. [6][7][8] Opioid analgesics cross the placenta and have potential to cause fetal harm.…”
mentioning
confidence: 99%
“…2,8,13 However, it may be difficult to identify higher risk groups in studies where POE is defined broadly. For example, although most people with POE are prescribed short courses of opioid analgesics in pregnancy, 2 those with long-term opioid analgesic use are at greater risk of developing OUD, 14 which may go undiagnosed because of stigma associated with drug use during pregnancy. Previous studies have identified factors associated with various types of opioid use in pregnancy using variable-centered approaches 5,11,13 (eg, regression analysis) that focus on associations between variables across people with an underlying assumption that variable associations are the same among all members in a population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, women in the United States have also reported tobacco use (11.6%), heavy alcohol use (9.9%), and illicit substance use (5.4%) during pregnancy 3 . Canadian women have also reported cannabis use (3.1%) and alcohol use (10%) during pregnancy 4,5 . Opioid use during pregnancy is likewise a problem in Canada 4,6 .…”
Section: Substance Use In the Perinatal Periodmentioning
confidence: 99%
“…Canadian women have also reported cannabis use (3.1%) and alcohol use (10%) during pregnancy 4,5 . Opioid use during pregnancy is likewise a problem in Canada 4,6 . Despite an overall decrease in prenatal opioid exposure from 2014 to 2019, Camden et al 6 discovered that the annual prevalence of prenatal opioid exposure was 4.5% of all hospital births in 2019, with the highest rates among women aged 20 to 24 years.…”
Section: Substance Use In the Perinatal Periodmentioning
confidence: 99%